The Role of Quantitative and Semi-quantitative [18F]FDG-PET/CT Indices for Evaluating Disease Activity and Management of Patients With Dermatomyositis and Polymyositis - Yildiz, Halil; D'abadie, Philippe; Gheysens, Olivier (Frontiers in Medicine, 2022)
Idiopathic inflammatory myopathies (IIM) are considered systemic diseases involving different organs and some subtypes are associated with increased cancer risk. In this review, we provide a comprehensive summary of the current use and potential applications of (semi-)quantitative [18F]FDG-PET/CT indices in patients with IIM focusing on dermatomyositis and polymyositis. Visual interpretation and (semi-)quantitative [18F]FDG-PET indices have a good overall performance to detect muscle activity but objective, robust and standardized interpretation criteria are currently lacking. [18F]FDG-PET/CT is a suitable modality to screen for malignancy in patients with myositis and may be a promising tool to detect inflammatory lung activity and to early identify patients with rapidly progressive lung disease. The latter remains to be determined in large, prospective comparative trials.